Exposure to wood smoke particles produces inflammation in healthy volunteers. Issue 3 (30th June 2011) - Ghio, Andrew J; Soukup, Joleen M; Case, Martin; Dailey, Lisa A; Richards, Judy; Berntsen, Jon; Devlin, Robert B; Stone, Susan; Rappold, Ana
Abstract : Objectives: Human exposure to wood smoke particles (WSP) impacts on human health through changes in indoor air quality, exposures from wild fires, burning of biomass and air pollution. This investigation tested the postulate that healthy volunteers exposed to WSP would demonstrate evidence of both pulmonary and systemic inflammation. Methods: Ten volunteers were exposed to filtered air and, 3 weeks or more later, WSP. Each exposure included alternating 15 min of exercise and 15 min of rest for a total duration of 2 h. Wood smoke was generated by heating an oak log on an electric element and then delivered to the exposure chamber. Endpoints measured in the volunteers included symptoms, pulmonary function tests, measures of heart rate variability and repolarisation, blood indices and analysis of cells and fluid obtained during bronchoalveolar lavage. Results: Mean particle mass for the 10 exposures to air and WSP was measured using the mass of particles collected on filters and found to be below the detectable limit and 485±84 μg/m 3, respectively (mean±SD). There was no change in either symptom prevalence or pulmonary function with exposure to WSP. At 20 h after wood smoke exposure, blood tests demonstrated an increased percentage of neutrophils, and bronchial and bronchoalveolar lavage revealed a neutrophilic influx. Conclusions: We conclude that exposure of healthy volunteers to WSP may be associated with evidence of both systemic and pulmonary inflammation.